A Proposal for Data Authentication, Data Integrity and Replay Attack Rejection for the Lin Bus - Kaschel-Carcamo, H; Paez-Mejias, F (Institute of Electrical and Electronics Engineers Inc., 2021)
Today s most relevant in-vehicle communication buses (CAN, LIN, FlexRay) offer no standard cybersecurity features, being highly vulnerable to local and remote cyberattacks, targeting the onboard computer and spreading to the vehicle s electronic control units through the aforementioned buses. Cybersecurity proposals for CAN and FlexRay have been introduced in the past, from various authors; no such proposal for the LIN (Local Interconnect Network) bus has been presented yet. This paper presents a computationally-feasible, real-time and hash-based message authentication code (HMAC) scheme, for the LIN bus. This proposal provides message integrity check and authentication, and uses a node s internal timestamp in order to reject replay attacks. © 2021 IEEE.